Quality of nursing work life, job satisfaction, and intent to leave among Jordanian nurses: A descriptive study - Muna Fayez Salahat; Zaid Mohammed. Al-Hamdan (Heliyon, 2022)
Background: Nurses’ intentions to leave their job are considered among the several difficulties encountered by any health system. Quality of nursing work life (QNWL) and job satisfaction are among the significant factors that impact this intention. Purpose: To explore the relationship between quality of work-life job satisfaction and the intention to leave among registered nurses (RNs) in Jordanian hospitals. Methods: A cross-sectional study using a self-administered questionnaire was conducted to collect data from 200 RNs from three hospitals in Jordan to measure the main variables from July 11 to 25,2020. Data were analyzed using descriptive and inferential statistics using SPSS version 25. Results: A total of 193 RNs participated in the study and were moderately satisfied with their quality of work life and job satisfaction. QNWL correlated positively with job satisfaction (r = 0.579, p = 0.000) and negatively with intent to leave (rs = - 0.204, p-value = 0.002). Job satisfaction was negatively correlated with the intent to leave (rs = - 0.174, p-value = 0.008). Sociodemographic and work-related variables (hospital type, sex, educational level, and salary) showed significant differences and correlations with at least one of the main variables. Conclusion: This study's results can be used by health care managers and policymakers to implement successful plans and policies to improve the QNWL and job satisfaction of RNs. This, in turn, may assist in enhancing individual and organizational performance; improving home and job environments; increasing nurses' commitment and increasing nursing retention. Further research is needed to develop effective measures for enhancing QNWL and job satisfaction among RNs.